Actualization And Inheritance Of Pabitte Passapu Art In Tanah Towa Village, South Sulawesi - Samidi; Husain, Sarkawi B. (Mudra Jurnal Seni Budaya, 2024)
The preservation of the traditional art of Pabitte Passapu faces challenges when there are changes in the community supporting the art, so that the inheritance of art to the younger generation is hampered. This condition disrupts the stability of the arts in the Kajang indigenous community. Therefore, the problem in this article is the efforts made by the Kajang indigenous community in maintaining the art of Pabitte Passapu so that the value and meaning of the art remain a source of learning. The objectives of this article are first, to explain that the Kajang indigenous people maintain local values in the midst of societal changes; second, to analyze the performance and meaning of the Pabitte Passapu dance as a source of learning local values; and third, to analyze the ability of the indigenous people to pass on the intellectual property contained in the Pabitte Passapu art. This research uses qualitative research methods. Data were collected through observation, in-depth interviews, oral history interviews, and documentation. Qualitative data analysis uses historical and socio-cultural approaches, especially dance sociology. The results showed that the preservation of the art of Pabitte Passapu can be done through the strategy of strengthening the space for the actualization of art, innovating the inheritance of art through learning and training.